Administrative Decentralization and Bureaucratic Reform ; India and Indonesia - Mason C Hoadley (Jurnal Administrasi Publik, 2014)
The paper compares the broad outlines of decentralization taking place in India, dating from the last decade of the past century, with that of Indonesia in the first decades of the present one. When appropriate, material from China will be included in the essay. Of the usual subjects of political, administrative, and physical decentralization, the center of focus is on the generally acknowledged least successful in terms of reform, i.e. the civil administration. What the approach lacks in specific details concerning administrative decentralization in the respective republics, it makes up for in the emphasis on the key characteristics of each. Moreover, as public administration tends to reflect the individual countries’ prevailing norms, such an approach tends to be influenced by a new range of literature and researchers whose views challenge accepted wisdom and inspire new lines of thinking on the subject. Justification for the approach comes from expectations that cross fertilization can inspire ideas for a ‘new paradigm and conceptual framework’, ultimately leading to corrective action. The predominance of corruption/dysfunctional administrative behavior is explained by the fact that it draws upon an on-going project dealing with corruption in India and Indonesia, a joint venture of the Humanistic and Economics Faculties at Lund University. Represented by among others the author and Prof. Neelambar Hatti, the project has its origins in an earlier Lund-Parahyangan University project on Public Administration (1999-2006).   The paper opens by listing several of the more important contrasts between Indian, Indonesian, and Chinese decentralization. These include governmental structure, respective colonial heritage, and the focus of decentralization efforts. A short summary of the process of decentralization drawing upon the work of the Lund corruption project follows. The heart of the paper is the question of whether administrative decentralization furthers, hinders, or is neutral with regard to bureaucratic reform in theory and practice. Weighing up successes and failures leads to consideration of continued, if not higher, levels of corruption/dysfunctional behavior at all levels. Possible improvements are postulated, not surprisingly originating from the application of principles derived from New Public Management (NPM), with a couple of new wrinkles from India. These and other types of reform depend on general public engagement, which is conspicuous by its absence in Indonesia, especially in comparison with India’s recent mass demonstrations, hunger-strikes, and high-level public condemnation of  (mega) public corruption. Key words:Administrative decentralization, bureaucratic reform, comparative public administration, corruption, India, Indonesia